FORMALIN: SEBUAH FENOMENA GUNUNG ES - Maman A. Djauhari (Fakultas Seni Rupa dan Desain ITB, 2008)
Formalin is famous because of its danger. Although it has some advantages, it may give disadvantages for the layman. Figuratively, the 'formalin' phenomena are pervasive. For example, the stinky garbage that blocks the drainage. Another example is found in our low quality television programs. The high dose of 'formalin' is also found in many of our mass media, particularly in Playboy magazine. Furthermore, the formalin phenomenon, has affected both the Indonesia's noblesse artists and the intellectuals. It is proved by the fact that the former rely on the misleading belief